PENDEKATAN BERBASIS TAFSIR AYAT-AYAT AL-QUR'AN DALAM MENYIKAPI PERUBAHAN SOSIAL DI BUKITTINGGI: PERSPEKTIF HUKUM ISLAM - Nabila Inita Zahra; M. Taufiq (Adisam Publisher, 2025)
Social changes in Bukittinggi, influenced by modernization and globalization, present challenges in maintaining Minangkabau cultural values amidst the demands of modern developments. This study aims to explore how Islamic law, through a contextual Qur'anic interpretation approach, can provide adaptive solutions in dealing with social dynamics in Bukittinggi society. Using a descriptive qualitative research method, this study highlights the role of interpretation based on maqashid sharia, which emphasizes the objectives of sharia such as preserving religion, soul, mind, descendants, and property, as the main foundation in responding to social change in a relevant and applicable manner. The results of the study indicate that collaboration between ulama and traditional leaders is a key factor in maintaining harmony between religious values and local traditions. This approach allows Islamic law to remain relevant as a flexible and contextual guide to life, so that society can adapt to change without sacrificing cultural and Islamic identity.